2011
DOI: 10.1590/s0102-33062011000300005
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes in Psidium guajava 'Paluma' leaves exposed to tropospheric ozone

Abstract: Structural changes in ABSTRACT(Structural changes in Psidium guajava 'Paluma' leaves exposed to tropospheric ozone). Psidium guajava 'Paluma' has being tested as an ozone (O 3 ) bioindicator and responds with pigmentation between the veins on the adaxial surface, due to the accumulation of phenolic compounds. Th ese compounds act as non-enzymatic antioxidants that neutralize reactive oxygen species (ROS), formed from O 3 . Th is study aimed to evaluate the leaf structure of plants with and without visible symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 22 publications
3
2
0
Order By: Relevance
“…As the storage period and the maturation process progressed, the anomalies started to become more noticeable, but restricted to the fruit epicarp. Similar symptoms were described by several researchers (FURLAN et al, 2007PINA & MORAES, 2007TRESMONDI & ALVES, 2011) when reporting the effect of ozone in 'Paluma'…”
Section: Resultssupporting
confidence: 83%
“…As the storage period and the maturation process progressed, the anomalies started to become more noticeable, but restricted to the fruit epicarp. Similar symptoms were described by several researchers (FURLAN et al, 2007PINA & MORAES, 2007TRESMONDI & ALVES, 2011) when reporting the effect of ozone in 'Paluma'…”
Section: Resultssupporting
confidence: 83%
“…As the storage period and the maturation process progressed, the anomalies started to become more noticeable, but restricted to the fruit epicarp. Similar symptoms were described by several researchers (FURLAN et al, 2007PINA & MORAES, 2007TRESMONDI & ALVES, 2011) when reporting the effect of ozone in 'Paluma' and 'Pedro Sato' guava fruits (MORAES et al, 2011). Therefore, the anomalies observed in the present study are in accordance with the standard found in the literature (SÁNCHES et al, 2002;NOVAK et al, 2003).…”
Section: Resultssupporting
confidence: 80%
“…As the storage period and the maturation process progressed, the anomalies started to become more noticeable, but restricted to the fruit epicarp. Similar symptoms were described by several researchers (FURLAN et al, 2007PINA & MORAES, 2007TRESMONDI & ALVES, 2011) when reporting the effect of ozone in 'Paluma' and 'Pedro Sato' guava fruits (MORAES et al, 2011). Therefore, the anomalies observed in the present study are in accordance with the standard found in the literature (SÁNCHES et al, 2002;NOVAK et al, 2003).…”
Section: Resultssupporting
confidence: 79%